(untitled) (Third Sector Social Economic Review, 2019)
This study examines the long and short run relationships between stock market indices of Turkey and G7 countries by employing Johansen Cointegration and Granger Causality analyses for the period after the 2008 global financial crisis. In particular, the 2008 financial crisis started in USA, a developed country, and spread all over the world has led investors to invest in different countries’ stock market indices in order to minimize portfolio risks. Therefore, the determination of both the long and short run relationships between different countries’ stock markets are very important in terms of portfolio management and diversification. The long-run results of the study show that it is still not possible to mention of a full integration,between stock market indices of Turkey and G7 countries, therefore with diversification it may be possible for international investors to provide a limited return by lowering risk. Besides, the Granger causality analysis concludes that in general the stock market indices of developed countries granger causes Borsa Istanbul.